Preparation of Pt/graphene catalysts for polymer electrolyte membrane fuel cells by strong electrostatic adsorption technique - S. Pothaya (2019)
© 2019 Hydrogen Energy Publications LLC The Pt/graphene catalysts were prepared by using strong electrostatic adsorption (SEA) technique for polymer electrolyte membrane fuel cell (PEMFC). The pH shift was considered and the point of zero charge (PZC) of graphene was acquired at pH about 5.2. Due to the mid-to-low PZC, the cationic precursor (i.e., platinum tetra-ammine ([NH3)4 Pt]2+ or PTA) was chosen. After graphene surface was treated to be anionic substrate, the PTA was added and adsorbed onto the graphene by electrostatic force. Pt metals between before and after adsorption were determined by inductively coupled plasma spectroscopy (ICP) in order to consider Pt percent weight. After reduction in hydrogen environment, Pt/graphene catalysts were made. The second adsorption including the reduction was repeated in order to obtain the high Pt percentage such as 21.5%wt. The average particle sizes (ca. 2.2 nm) and distribution of Pt were inspected using transmission electron microscopy (TEM), where the crystalline structures were verified by X-Ray diffraction (XRD). Electrochemical properties were tested using cyclic voltammetry (CV) and the accelerated durability test (ADT) was also carried out. The oxygen reduction reaction (ORR) was also carried out, where the specific activity and mass activity were examined. It was observed from ADT that mass activity lost about 33%. Furthermore, the ORR was performed to verify the first order reaction, as well as to determine the mechanism path way for four electron transfer. Moreover, the kinetic constant of the ORR was also estimated.